Demand for food safety attributes of vegetables in the Klang Valley, Malaysia - Khalid, Joya (2020)
Due to the relation between food and health, food safety is receiving greater attention from consumers. Increasing in income and urbanization have changed the consumers’ demand and preferences towards food safety attributes. Meanwhile in recent years, the vegetables’ farmers in Malaysia has been reported of using excessive quantity of pesticides in order to increase the production. In 2015, some 300 batches of vegetables mostly leafy vegetables were stopped f rom being sold in Singapore after pesticide residues found on samples exceeded levels allowed by the authorities. Also, in 2017, vegetables from Cameron Highlands have been rejected from China due to the presence of excessive level of pesticides. In 2018 there was a recall of iceberg lettuce from Agri-Food and Veterinary Authority of Singapore (AVA) due to the excessive chemicals used. These incidences have created a concern to improve the safety of vegetables produce. Nowadays due to changing in life style as well as urbanization and increasing in incomes the consumers are more conscious about their health and they sharpen their attention to the safety attributes of food. Therefore, this study was conducted to determine the demand for food safety attributes of vegetables in Malaysia. Three types of vegetables such as leafy vegetables (Cabbage), root vegetables (Carrot), and fruit vegetables (Tomato) have been included in this study. Discrete choice experiment has been used to estimate the demand for food safety attributes of vegetables. A focus group discussion was done in order to determine the most relevant safety attributes before creating the choice sets. From the focus group discussion, it was found that appearance, production system, type of market, Malaysian Good Agricultural Practice (MyGAP) certification, and price were the most important safety attributes for vegetables. Proportionate sampling method was used to select the respondents in Klang Valley area. 505, 490 and 490 respondents have completed the survey for cabbage, carrot and tomato, respectively. Using the choice experiments, the respondents were asked about what type of vegetables that they would buy among the orthogonally designed choice sets. The results showed that in terms of food safety attributes, Malaysian consumers prefer wholesome appearance rather than slightly damage, organic rather than conventional, sold at the supermarket rather than wet market and vegetables with MyGAP certification rather than not certified vegetables. In addition, results suggested that Malaysian consumers are willing to pay a premium for food safety attributes of vegetables. The findings also indicated that the willingness to pay varied according to income, education level and age. The higher willingness to pay for food safety attributes indicate that the consumers are paying more attention to the safer product. Therefore, policies on food safety should be pursued and supported by Malaysian government in order to enhance the safe food market, which it would be beneficial for all consumers. Since the consumers are willing to pay for safer attributes, if the industry and farmers can respond effectively to these changes it can be translated into business opportunities.